FOSTERING LEARNERS' AUTONOMY IN WRITING - Christiana Sidupa (Journal of English Education, 2016)
In studying English as Second Language (ESL), learners’ autonomy is needed. As we know, learner autonomy has been claimed to be an ultimate goal of education for a long time and has been identified as a complicated capacity that potentially has a great impact on personal growth and achievement. The autonomy positively affects language learning and it is no doubt that learners’ autonomy is a prerequisite for effective language learning. This qualitative research aimed to describe the strategies to foster learners’ autonomy in writing class. Participants consisted of students at Bina Nusantara University. Qualitative research was conducted because the researcher wanted to understand the context or setting in which the participants of the study addressed an issue connected with the strategies to promote the learners’ autonomy in writing. The result showed that there were two strategies that foster learners’ autonomy in writing class that covered the uses of Computer-Assisted Language Learning (CALL) and student-centered approach.